Belongingness in Medical Student Placements: Validation and Pilot Study of the Use of the Exeter Belongingness Assessment Tool in Belgian and English Medical Students - Rob Daniels; Thomas Pattyn; Birgitte Schoenmakers; Eric Buramba; Kato Denis (Journal of Medical Education and Curricular Development)
BACKGROUND Belongingness is an important factor in the social development of medical students, and the ability to quantify belongingness in medical students may provide additional metrics by which we can compare different learning environments to help explore differential attainment. Previous studies looking at the measurement of belongingness have demonstrated good internal and external validity for tools designed to measure this facet of student experience. This study aimed to explore the use of the Exeter Belongingness Assessment Tool (EBAT) as one potential source of evidence in the study of student learning experience on clinical placements, which could be used to support quality assurance of clinical learning. This study sought to validate the use of the EBAT and carry out an initial pilot study to compare levels of belongingness in medical students in Belgium and the United Kingdom. METHODS This study used a validated assessment tool self-administered via an online survey platform in undergraduate medical students in all years studying in Belgium and the United Kingdom. RESULTS The EBAT described here demonstrated good internal validity in undergraduate medical students in the United Kingdom and Belgium and identified statistically significant differences between these medical student populations . CONCLUSIONS These results suggest that belongingness in undergraduate medical students varies between different demographic groups and provides further evidence that the EBAT described here is a valid tool to study this. It also supports the proposal that this may be a useful tool to monitor teaching environments.